Hydrosaline solutions - Suárez, Raúl A (Cirugía del Uruguay, 1973)
The mora outstanding properties of hydrosaline solutions are considered, with stress on the fact that they facilitate miocardial function as a mechanic pump. Molar solutions, their management and reduced water volume employed are mentioned, Hydrosaline solutions should cover water and electrolitic requirements, previous deficits, anticipated losses and additional pathological losses. With respect to the manner of administering them, wme. should be administered early and rapidly, while others require diferred and slow methods.